2009
DOI: 10.1007/s12149-009-0292-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of 18F-FDG PET/CT in the differentiation of pulmonary artery sarcoma and pulmonary embolism

Abstract: FDG PET/CT could distinguish pulmonary artery sarcoma from pulmonary embolism based on the SUV(max) value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 16 publications
3
69
0
1
Order By: Relevance
“…In this case, FDG-PET and chest radiography were useful in a diagnostic workup, as has been reported elsewhere. 4 There is no specifi c guideline on the management of pulmonary artery sarcomas. The standard therapeutic procedure is surgical resection with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, FDG-PET and chest radiography were useful in a diagnostic workup, as has been reported elsewhere. 4 There is no specifi c guideline on the management of pulmonary artery sarcomas. The standard therapeutic procedure is surgical resection with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the diagnostic usefulness of 18 F-fl uorodeoxyglucose (FDG)-PET in differentiating pulmonary artery sarcoma and pulmonary embolism has been reported. 4 We describe the case of a pulmonary arterial intimal sarcoma that underwent serial FDG-PET studies for monitoring the therapeutic response.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple PET findings have been described in association with pulmonary emboli, including pulmonary artery hypermetabolism (13,(22)(23)(24), four-chamber cardiac uptake (25), and the presence of a rim of hypermetabolism surrounding a pulmonary infarction (26,27). However, the relative frequency of these findings has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…We found that focal pulmonary arterial hypermetabolism could only be qualitatively detected in 15.2% of cases, indicating that this is an insensitive secondary sign of PE. The differential diagnosis for the finding of pulmonary arterial hypermetabolism includes pulmonary artery sarcoma, pulmonary artery metastasis, and FDG microembolism secondary to paravenous injection (23,24,28). These should be readily distinguishable because of the much higher SUV reported for pulmonary artery malignancies, and because of the presence of extravasation of FDG at the injection site in the case of microembolism.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the FDG PET/CT procedure have been previously described [19,22]. Patients fasted overnight for at least 4 h, and normal blood glucose level was confirmed before FDG injection.…”
Section: Fdg Pet/ct Examinationmentioning
confidence: 99%